ChemInform Abstract: Ferromagnetism Induced by Substitution of the Iron(IV) Ion by an Unusual High‐Valence Nickel(IV) Ion in Antiferromagnetic SrFeO3. Issue 14 (March 2016) - Seki, Hayato; Hosaka, Yoshiteru; Saito, Takashi; Mizumaki, Masaichiro; Shimakawa, Yuichi
Abstract: SrFe1‐x Nix O3 (x = 0, 0.1, 0.2, 0.4, 0.5) with unusual high‐valence Fe IV and Ni IV ions are obtained by calcining stoichiometric amounts of Fe2 O3 and NiO in air (1273 K, 1 d) followed by hot press sintering of the latter with appropriate amounts of SrO2 and KClO4 (Pt capsule in multianvil apparatus, 1273 K, 10 GPa (x = 0—0.2) or 15 GPa x = 0.4 and 0.5).